Respon Petani Padi Rawa Lebak Terhadap Rencana Pembentukan Komunitas Estate Padi Di Desa Sungai Dua Kecamatan Rambutan Kabupaten Banyuasin - Muhammad Andri Zuliansyah; Acip Rakhmat (Program Studi Agribisnis Universitas Sumatera Selatan, 2022)
The Rice Estate Community (KEP) is formed by small-scale farmers in an overlay in an area by adhering to the principles of synergy, consolidation, togetherness, and sustainability. KEP is built in order to increase farming efficiency, income and welfare of farmers. Through KEP modern rice production systems, mechanization, best practice applications that are precise, controlled, and sustainable (sustain) can be achieved. This study aims to 1) describe the implementation of the KEP formation plan, 2) identify farmers' responses to the formation of KEP based on 3 indicators (cognitive, affective, and conative). The method used in this research is by using survey method. Sampling method with the census. The results showed that 1) In its implementation, KEP synergizes with other institutions to support the smooth running of KEP management. KEP will initially develop a rice business. After the rice business is running well, KEP can develop other businesses not only rice but also seed production business, provision of production facilities, organic fertilizer business, Alsin workshop service business, Alsin service management business (UPJA), and other side businesses. 2) Farmers' response to the KEP formation plan seen from 3 indicators, namely cognitive with an average score of 29.17 with agreed criteria, affective with an average score of 26.13 with agreed criteria, and conative with an average score of 27.10 with agreed criteria.